Exemplification of catalyst design for microwave selective heating and its application to efficient in situ catalyst synthesis - Wang, Kaiyang; Dimitrakis, Georgios; Irvine, Derek J. (Elsevier, 2017)
The use of dielectric spectroscopy to develop an underpinning understanding of the molecular transformations involved in achieving the successful, rapid in situ synthesis of a catalytic chain transfer polymerisation (CCTP) catalyst using microwave heating is reported. The hypothesis behind the molecular design of this catalyst, such that it was tailored towards the application of microwave heating (MWH), is discussed, reviewed relative to the empirically results and compared to the performance of a benchmark preformed catalyst. The overall number/type of function group present in the catalyst, the degree of flexibility exhibited by its organic ligand system and level of solvation achieved are shown to be key factors affecting the interaction between the catalyst and the applied microwave energy. Use of microwave heating leads to fast, in situ formation of the catalyst (less than 30 second) within the polymerisation mixture, rendering prepreparation steps unnecessary and ensuring it is generated prior to the polymerisation reaction commencing. The data also suggests catalysts’ synthesis is achieved at levels of microwave power as low as 5 Watts, further adding to the efficiency and sustainability of the method and presents a potentially enormous opportunity to intensify current industrial processes.